10GHz regeneratively mode-locked erbium-doped fiber laser combined with nonlinear amplifying loop mirror. Issue 1 (May 2021) - Liang, Ke; Zhou, Yue; Xu, Kun
Abstract: Mode-locked fiber lasers can generate short pulses with a high repetition rate. It can be used in nonlinear optical imaging, photo-communication and other fields. Obtaining narrow pulses with high repetition frequency has become a hot research topic. In this article, we demonstrate a hybrid mode-locked fiber laser, which is a regeneratively mode-locked erbium fiber laser operating at 10 GHz, incorporating a nonlinear amplifying loop mirror to generate a 1.9 ps pulse sequence. This all-fiber laser with a high-repetition-rate and short pulses has the advantages of high stability and self-starting, which has a wide range of applications.